Presenteeism among Governmental Office Workers-Using VDT and Associated Risk Factors - Citra Nurhayati Sjarifuddin; Marsen Isbayu Putra; Dewi Sumaryani Soemarko; Dewi Friska; Nuri Purwito Adi (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Background: Presenteeism is the presence of workers in the workplace without full working capacity due to health factors, but several studies also link it to organizational influence. The government staffing system in Indonesia has two types of work status (permanent and non-permanent) and policy changes related to increasing the use of Visual Display Terminal (VDT), will certainly affect worker presenteeism. This study was conducted to assess the risk factors presenteeism in workers using VDT in the Indonesian government office. Methods: This study was a cross-sectional observational study using a questionnaire method using the Stanford Presenteeism Scale (SPS-6) to assess presenteeism and its association with organizational and health risk factors in a multivariate manner. Computer Vision Syndrome (CVS) at one of associated factor, was assessed using Indonesian version of CVS Questionnaire (CVSQ). Analysis of this study used SPSS version 26. Results: Of the 201 research subjects, 44.28% of presenteeism was found. but complaints of computer vision syndrome (Positive CVSQ score) were found in almost all of the study subjects (84.5%). Risk factors for employment status and position have a strong relationship with presenteeism (p <0.001). Temporary worker status has a 7.08x risk (aOR=7.08 95% CI = 3.1-15.8) of experiencing presenteeism. Whereas for workers with a presenteeism risk position of 3.45x (aOR=3.45 95% CI = 1.3-8.5). Conclusion: Most government workers who use VDT continue to work even though they have health problems in the form of complaints of computer vision syndrome. Non permanent status (aOR=7.08 95% CI = 3.1-15.8) and low position (aOR=3.45 95% CI = 1.3-8.5) are determinant factors for presenteeism.